RESISTANCE EVALUATION ON POPULATIONS OF CROSSES BETWEEN TRANSGENIC POTATO KATAHDIN RB AND NON-TRANSGENIC ATLANTIC AND GRANOLA TO LATE BLIGHT (Phytophthora infestans) IN CONFINED FIELD TRIAL - Ambarwati, Alberta Dinar; Herman, Muhammad; Purwito, Agus; Sumaraw, Sientje Mandang; Aswidinnoor, Hajrial (Indonesian Agency for Agricultural Research and Development - MOA, 2011)
Late blight resistance gene (RB gene) isolated from Solanum bulbocastanum, is a broad resistance gene against all races of Phytophthora infestans. The gene was transformed into Katah-din event SP904 and SP951 using Agrobacterium tumefaciens and these transgenic plants have been crossed with susceptible potato cultivars Atlantic and Granola. Populations of the crosses have been molecularly characterized for the integration of the RB transgene. The study aimed to evaluate the resistance of the populations of crosses between transgenic Katahdin RBÂ and susceptible non-transgenic parents (Atlantic and Granola) to late blight in a confined field trial at Pasir Sarongge, Cianjur, West Java. A total of 84 clones originated from four popula-tions were evaluated for resistance to late blight. These included 22 clones of Atlantic x transgenic Katahdin SP904, 16 clones of Atlantic x transgenic Katahdin SP951, 19 clones of Granola x transgenic Katahdin SP904, and 27 clones of Granola x transgenic Katahdin SP951. Observations of the late blight infection were conducted when late blight symptoms were detected, i.e. at 56, 60, 63, 70, and 77 days after planting (DAP). The result showed there were high variations in the resistance level of all the 84 clones tested. Clones of crosses between susceptible parents (Atlantic or Granola) and resistant parents (transgenic Katahdin SP904 or Katahdin SP951) showed a similar pattern based on the area under disease progress curve (AUDPC) value, i.e. 377.2 greater than the AUDPC of the resistant parents (180.1), but smaller than that of the susceptible parents (670.7). Observation at 77 DAP resulted four resistant potato clones having resistance score of 7.0-7.6, higher than the transgenic parents Katahdin SP904 (4.6) and Katahdin SP951 (6.8), i.e. clone B8 (Atlantic x transgenic Katahdin SP951) with resistance score of 7.6 and clones B26 (Atlantic x transgenic Katahdin SP951), C183 (Granola x transgenic Katahdin SP904), and D89 (Granola x transgenic Katahdin SP951) with resistance score of 7. These four transgenic potato resistant clones need to be further developed as promising potato clones to late blight.